Consequences of COVID-19 preventive measures on anxiety, stress and depression in football athletes - de Souza, G.; dos Santos, W.; Paes, P.; Fidelix, Y.; de Paula Oliveira, L.; da Costa, M. (Soccer & Society, 2022)
The study analysed the impacts of the preventive measures of COVID-19 on the symptoms of anxiety, stress and depression in soccer athletes. Twenty-four males participated in the study, with an average age of 18.4±1.4 years, who had their training suspended due to the preventive measures of COVID-19. Levels of anxiety, stress and depression (DASS-21) and competitive anxiety (CSAI-2 R) were assessed during training interruption and 20 days after the laps. The return to training, after the training interruption period, reduced the levels of somatic anxiety (10.6%), cognitive anxiety (10.5%), depression (9.8%), stress (19.7%), anxiety (14.2%) and self-confidence (4.8%), but without significant differences. It was identified that athletes with more than 10 years of practice had a significant increase in confidence (p =0.009) compared to athletes with less than 10 years of practice. During the pandemic, there was no variation in the levels of anxiety, stress and depression symptoms in athletes.